Patterns of remission from alcohol dependence in the United Kingdom: results from an online panel general population survey - John A. Cunningham; Christina Schell; Hollie Walker; Alexandra Godinho (BMC, 2024)
Abstract Background Previous research has demonstrated that remissions from alcohol use disorders can occur without accessing treatment. The current study explored the prevalence of such untreated remissions in the UK and further, examined the extent to which people who resolved an alcohol use disorder regarded themselves as ever, or currently, being in recovery. Methods Participants were recruited using the Prolific online platform. Participants who met criteria for lifetime alcohol dependence (ICD-10) were asked about their drinking at its heaviest, use of treatment services, whether they identified as being in recovery, and their current alcohol consumption (to identify those who were abstinent or drinking in a moderate fashion). Results A total of 3,994 participants completed surveys to identify 166 participants with lifetime alcohol dependence who were currently abstinent (n = 67) or drinking in a moderate fashion (n = 99). Participants who were currently abstinent were more likely to have accessed treatment than those who were currently moderate drinkers (44.4% versus 16.0%; Fischer's exact test = 0.001). Further, those who were abstinent were heavier drinkers prior to remission [Mean (SD) drinks per week = 53.6 (31.7) versus 29.1 (21.7); t-test = 5.6, 118.7 df, p < .001] and were more likely to have ever identified themselves as 'in recovery' (51.5% versus 18.9%; Fischer's exact test = 0.001) than current moderate drinkers. Conclusions While participants with an abstinent remission were more likely than those currently drinking in a moderate fashion to have accessed treatment and to identify as being 'in recovery,' the majority of participants reduced their drinking without treatment (and did not regard themselves as in recovery).